Natural history and aggravating factors of sagittal imbalance in marked sagittal deformity compared with mild to moderate sagittal deformity: A prospective cohort study. Issue 11 (March 2020) - Moon, Bong Ju; Ryu, Dal Sung; Kim, Byeongwoo; Ha, Yoon; Yoon, Seung Hwan; Kim, Keung Nyun; Chin, Dong Kyu; Lee, Jung-Kil
Abstract : Abstract: Sagittal imbalance is a multifactorial complex deformity that can arise from a variety of causes such as spinal stenosis, sarcopenia, vertebral fracture, and neuromuscular diseases. Furthermore, there is lack of research regarding spinal and general conditions that precede the development of sagittal imbalance. Our aim was to evaluate aggravating factors, such as natural history, for sagittal imbalance in a cohort comprising elderly individuals by conducting various examinations. We recruited 96 participants who had a sagittal vertical axis (SVA) larger than 50 mm in a sagittal imbalance study. Finally, 69 participants were followed up and enrolled this study after 2 years. We evaluated full spine radiographs, magnetic resonance imaging (MRI), bone mineral density, and health-related quality of life from patients survey and analyzed factors associated with aggravation of sagittal imbalance. Aggravation was defined by an SVA > 30 mm and T1 pelvic angle (T1PA) > 3° in the third year compared to SVA and T1PA values of the first year. Eighteen participants of the follow-up group had a sagittal imbalance aggravation. According to the deformity severity in the first-year evaluations, the marked deformity group (38 participants) defined as Schwab classification had 11 (28.9%) participants presenting with sagittal imbalance aggravation. These participants had larger mean values of Schwab sagittal modifiers and T1PA compared with the nonaggravation participants. Logistic regression analysis showed a higher pelvic incidence (PI) (OR = 1.201, 95% CI = 1.015–1.422, P  = .033) and a small multifidus (MF) volume (OR = 0.991, 95% CI = 0.983–1.000, P  = .043) correlated with sagittal imbalance aggravation. From the follow-up group, 18 (26%) subjects of total 69 participants presented a deteriorated sagittal imbalance. A higher PI and smaller MF volume correlated with the aggravation of sagittal imbalance. We should consider that high PI and small MF volume are associated with aggravation of sagittal imbalance.